1996
DOI: 10.1097/00006123-199607000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Uptake of Carboplatin and Survival in Glioma-bearing Rats by Intracarotid Infusion of Bradykinin Analog, RMP-7

Abstract: Intracarotid infusion of RMP-7 can selectively increase transport of carboplatin into brain tumors and results in higher survival in rats with gliomas. These findings support the use of intracarotid infusion of RMP-7 to enhance the delivery of carboplatin to patients with malignant brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
71
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 39 publications
1
71
1
Order By: Relevance
“…The pattern of viral delivery noted here, combined with the HSV-tk/GCV bystander activity, should help eradicate locally invasive tumor or micrometastases distal from the main tumor mass. RMP-7, like other vasoactive agents such as BK, histamine, and leukotrienes, 21,22,27,35 can selectively open the BTB by increasing the permeability of brain tumor capillaries, which are morphologically different from normal brain capillaries. RMP-7 has been used previously to enhance the delivery of chemotherapeutic agents to brain tumors and is approved for human use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pattern of viral delivery noted here, combined with the HSV-tk/GCV bystander activity, should help eradicate locally invasive tumor or micrometastases distal from the main tumor mass. RMP-7, like other vasoactive agents such as BK, histamine, and leukotrienes, 21,22,27,35 can selectively open the BTB by increasing the permeability of brain tumor capillaries, which are morphologically different from normal brain capillaries. RMP-7 has been used previously to enhance the delivery of chemotherapeutic agents to brain tumors and is approved for human use.…”
Section: Discussionmentioning
confidence: 99%
“…This result is probably not surprising given the large load of virus that was injected and the somewhat leaky nature of the BTB itself. 26,27 Clearly, however, intracarotid infusion of RMP-7 augmented the delivery of virus to experimental brain tumors without increasing the amount of virus delivered to the normal brain. Importantly, disruption of the BTB using RMP-7 promotes vector uptake into the infiltrating edge of brain tumors, which is an area that is difficult to distinguish from the normal brain by the conventional treatment modalities of surgery, chemotherapy, or radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing in animal models of glioma Elliott et al, 1996aElliott et al, , 1996bElliott et al, , 1996cMatsukado et al, 1996Matsukado et al, , 1998, as well as imaging studies in glioma patients (Warkne et al, 1995;Ford et al, 1996;Black et al, 1997) have demonstrated that Cereport not only increases permeability of the vasculature supplying brain tumours, but does so selectively. That is, the increased permeability is approximately 10-20 times greater in brain areas associated with tumours, as compared to normal, nontumour brain .…”
mentioning
confidence: 99%
“…More recently, bradykinin (Black, 1995;Matsukado et al, 1998;Nomura et al, 1994) and the bradykinin agonist Cereport Âź (RMP-7) (Bartus et al, 1996a, b;Doctrow et al, 1994;Straub et al, 1994) have been used to stimulate the receptors on the endothelial cells comprising the BBTB to increase barrier permeability. Cereport selectively increases permeability of the vasculature supplying brain tumors in rodent models of glioma (Bartus et al, 1996a, b; Elliott et al, 1996a, b;Matsukado et al, 1996) as well as in glioma patients Cloughesy et al, 1999;Ford et al, 1996).A potentially complicating factor with Cereport, or any pharmacologic approach intended to temporarily increase the permeability of the BBTB, is the possible interaction with other drugs commonly administered to glioma patients. For example, brain tumor patients typically receive corticosteroids, such as dexamethasone (Decadron Âź ), to treat emesis and manage neurologic symptoms by decreasing intracranial pressure (reviewed in Glaser et al, 1997;Gutin, 1977;Koehler, 1995;Vecht and Verbiest, 1995).…”
mentioning
confidence: 99%